2020
DOI: 10.5130/ajceb.v20i4.7366
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between contractor satisfaction and project management performance

Abstract: Despite the fast growth of project-based companies and industries, studies of the satisfaction-performance (S-P) nexus of project participants are lacking. This study aims to explore the role of contractor satisfaction in affecting contractor project management performance along with considering external effects from other key participants. Two broad dimensions of satisfaction toward noneconomic factors and economic factors were used to develop hypothesized models. Structural equation modelling techniques were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Based on the interrelations and the feedback, the ANP allows the calculation of the overall importance of criteria and the overall perspective level of every sub-factor [37,38]. The final step involves evaluating the user perspective level for a sustainable building using the user responses collected on a 5-point Likert scale: very dissatisfied, dissatisfied, medium, satisfied, and very satisfied [39][40][41]. In this regard, the users' perspective levels are demonstrated in the form of fuzzy membership functions to simulate the uncertainties linked with experts' judgements.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Based on the interrelations and the feedback, the ANP allows the calculation of the overall importance of criteria and the overall perspective level of every sub-factor [37,38]. The final step involves evaluating the user perspective level for a sustainable building using the user responses collected on a 5-point Likert scale: very dissatisfied, dissatisfied, medium, satisfied, and very satisfied [39][40][41]. In this regard, the users' perspective levels are demonstrated in the form of fuzzy membership functions to simulate the uncertainties linked with experts' judgements.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Xiong et al (2014) discussed that previous satisfaction research in the construction industry was concerned more about client satisfaction, carried out a study in Malaysia, and proposed a contractor selection model based on structural education modeling. Skitmore et al (2020) explored the role of contractor satisfaction in affecting contractor project management performance along with considering the external effects of other key participants. The study applied structural equation modeling techniques and found that it was insufficient to conclude contractor satisfaction influences project managerial performance or vice versa and satisfaction disaggregation was required.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This process is repeated until no significant independent variables are selected into the regression equation, and all insignificant independent variables are eliminated from the regression equation. Based on this, the BIM technology tunnelling parameters and the combination of tunnelling parameters and rock strength are respectively subjected to multiple stepwise regression [11]. Stepwise regression's calculation and implementation process is still automatically completed on the computer using SPSS software to obtain model 3 and model 4.…”
Section: Multiple Stepwise Regressionmentioning
confidence: 99%